Cysteine-10 on 17β-Hydroxysteroid Dehydrogenase 1 Has Stabilizing Interactions in the Cofactor Binding Region and Renders Sensitivity to Sulfhydryl Modifying Chemicals - Nashev, Lyubomir G.; Atanasov, Atanas G.; Baker, Michael E.; Odermatt, Alex (International Journal of Cell Biology, 2013)
17β-Hydroxysteroid dehydrogenase type 1 (17β-HSD1) catalyzes the conversion of estrone to the potent estrogen estradiol. 17β-HSD1 is highly expressed in breast and ovary tissues and represents a prognostic marker for the tumor progression and survival of patients with breast cancer and other estrogen-dependent tumors. Therefore, the enzyme is considered a promising drug target against estrogen-dependent cancers. For the development of novel inhibitors, an improved understanding of the structure-function relationships is essential. In the present study, we examined the role of a cysteine residue, Cys10, in the Rossmann-fold NADPH binding region, for 17β-HSD1 function and tested the sensitivity towards sulfhydryl modifying chemicals. 3D structure modeling revealed important interactions of Cys10 with residues involved in the stabilization of amino acids of the NADPH binding pocket. Analysis of enzyme activity revealed that 17β-HSD1 was irreversibly inhibited by the sulfhydryl modifying agents N-ethylmaleimide (NEM) and dithiocarbamates. Preincubation with increasing concentrations of NADPH protected 17β-HSD1 from inhibition by these chemicals. Cys10Ser mutant 17β-HSD1 was partially protected from inhibition by NEM and dithiocarbamates, emphasizing the importance of Cys10 in the cofactor binding region. Substitution of Cys10 with serine resulted in a decreased protein half-life, without significantly altering kinetic properties. Despite the fact that Cys10 on 17β-HSD1 seems to have limited potential as a target for new enzyme inhibitors, the present study provides new insight into the structure-function relationships of this enzyme.